If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -4) + 8(x + 2) = 0 Reorder the terms: 3(-4 + x) + 8(x + 2) = 0 (-4 * 3 + x * 3) + 8(x + 2) = 0 (-12 + 3x) + 8(x + 2) = 0 Reorder the terms: -12 + 3x + 8(2 + x) = 0 -12 + 3x + (2 * 8 + x * 8) = 0 -12 + 3x + (16 + 8x) = 0 Reorder the terms: -12 + 16 + 3x + 8x = 0 Combine like terms: -12 + 16 = 4 4 + 3x + 8x = 0 Combine like terms: 3x + 8x = 11x 4 + 11x = 0 Solving 4 + 11x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 11x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + 11x = 0 + -4 11x = 0 + -4 Combine like terms: 0 + -4 = -4 11x = -4 Divide each side by '11'. x = -0.3636363636 Simplifying x = -0.3636363636
| 4b-7=11b | | -7(n-1)=-6n-8 | | -3x-4y=6 | | 6x^2=8x^3 | | (-5)+(-4)+(7)= | | 10K-24=10k-26 | | x^2+11x+32=4 | | 6x^2-4x^3-.5=0 | | 7(x+3)= | | 6x+y=-4 | | 12x^2+11x=5 | | 3(4t+5)-6=9(t+2) | | c^2=121 | | 33=7+12+c | | 6r*s*4rt= | | y=-1.4x^3 | | 4x+(3+3x)= | | 4[2-(2x-5)]=2(12-3x) | | 6-(-2)-3(-5)= | | 16(p-2)=7p+4 | | -6x-2=(3x+1) | | 9x-2=5(x+1)+4x-7 | | 4m-3=15 | | 3x+12=-53-10x | | 2a+3=16 | | 6+3x=30 | | 7y+10-3y=-14 | | 3(5y+5)=51 | | 5m-13n-n+4m= | | 6x+6+5x-8= | | 104-7x=29x+20 | | 3f-2=f |